A Rare Case Report of Advanced Surgical Management of Proximal Tibia Giant Cell Tumor in a 20-year-old Girl-Extended Curettage and Sandwich Technique - M Harishkumar; B Mohan Choudhary; Arjun Ganesh; Kevin Lourdes (Journal of Orthopaedic Case Reports)
Introduction: Giant cell tumor (GCT) of bone is a benign but locally aggressive neoplasm, commonly affecting the epiphysio-metaphyseal regions of long bones in young adults. The proximal tibia is among the most frequent sites. Management is challenging due to the tumors high recurrence potential and its location near weight-bearing joints. Case Report: A 22-year-old female presented with a 5-month history of pain and swelling over the right knee. Imaging revealed an epiphysio-metaphyseal osteolytic lesion in the proximal tibia with an anterior cortical breach, confirmed on computed tomography and magnetic resonance imaging. Surgical management included extended intralesional curettage through an anteromedial approach. The tumor cavity was treated with high-speed burr, hydrogen peroxide lavage to prevent local recurrence and filled the cavity using sandwich technique with polymethyl methacrylate bone cement and gel foam. Results: Post-operative recovery was better. The patient was started on partial weight-bearing in 1 week and full weight-bearing by 2 weeks. Patient achieved nearly the full range of movements at the knee by 8 weeks. Histopathology confirmed the diagnosis of GCT. At 1-year follow-up, the patient showed no clinical or radiological signs of recurrence, with an excellent functional outcome. Conclusion: Extended curettage with adjuvant therapy and bone cementing through the sandwich technique offers a joint-preserving and effective treatment for GCTs of the proximal tibia, even in the presence of cortical breach. A long-term follow-up is essential to monitor for local recurrence or pulmonary metastasis.